A171 GERD IS NOT ASSOCIATED WITH JACKHAMMER ESOPHAGUS. (15th March 2019) - Woo, M; Liu, A; Wilsack, L; Buresi, M c; Curley, M; Gupta, M; Li, D Y; Andrews, C N
Abstract: Background: Dysphagia and non-cardiac chest pain are common referrals for esophageal motility testing. Hypertensive esophageal peristalsis, previously classified as "nutcracker esophagus, " has been re-labelled as "jackhammer esophagus" by the Chicago Classification of esophageal motility disorders (CC v3.0). Although the pathophysiology of jackhammer esophagus (JE) has yet to be elucidated, gastroesophageal acid reflux (GERD) has been implicated as a possible causative factor, based on the higher than expected incidence of GERD on patients with JE that has been seen in previous studies (43 - 47%). Aims: The aim of this present study is to determine if GERD is associated with JE when compared to symptomatic controls with normal HRM. Methods: Consecutive symptomatic patients who were referred for esophageal high-resolution manometry (HRM) studies in Calgary, AB from Nov 2013 to Sept 2018 were retrospectively analyzed. Patients with a manometric diagnosis of Jackhammer esophagus by CC v3.0 (≥ 2 hypercontractile swallows with distal contractile integral [DCI] > 8000 mmHg-s-cm) who also underwent ambulatory pH studies were compared to patients with normal HRM (controls). Groups were compared with Pearson's chi-square testing and ANOVA as appropriate. This study was IRB approved. Results: 20 JE patients and 82 controls who underwent both HRM and ambulatory pH testing were identified. Age and gender breakdown were similar between both groups (see Table 1). The most common presenting complaint in the JE group was dysphagia (35.0%) and in controls was heartburn (26.8%). Similar numbers of both groups were on PPI (50.0% JE, 51.2% controls). 3 (25.0%) JE patients and 14 (17.1%) controls had evidence of abnormal acid exposure on 24h ambulatory pH study (defined as DeMeester score > 14.7); this difference was not significant ( p = 0.56). When abnormal acid exposure was defined as acid exposure time (AET) > 4.2%, there was no significant difference seen between both groups ( p = 0.50). There were no significant differences seen between other parameters of the DeMeester score (see Table 1). Conclusions: Abnormal acid exposure on ambulatory pH study does not appear to be associated with JE, when compared to patients with normal HRM. This finding suggests that abnormal esophageal acid exposure is unlikely to be a causative factor for the peristaltic abnormalities seen in Jackhammer esophagus. Funding Agencies: None